Answer:
Step-by-step explanation:
Answer:
300
Step-by-step explanation:
Answer:
y=-2/7x+1
Step-by-step explanation:
m=(y2-y1)/(x2-x1)
m=(-5-(-1))/(21-7)
m=(-5+1)/14
m=-4/14
simplify
m=-2/7
y-y1=m(x-x1)
y-(-1)=-2/7(x-7)
y+1=-2/7(x-7)
y=-2/7x+2-1
y=-2/7x+1
The only way to do this is by long division of polynomials. That's because the quadratic doesn't factor with real numbers and you can't cancel out from numerator to denominator. Set up your problem with the x-squared term inside the division box and the x + 6 outside. It's quite impossible to demonstrate long division in this forum, so your answer is going to be x-7 R3. I do suggest you learn this, though, as it is very important as you advance in your math classes in school.